Doing Business in Mexico 2012 - World Bank; International Finance Corporation (Washington, DC, 2013)
Mexico is a country open to international trade. It has already signed 11 free trade agreements with 43 economies. The advantages of Mexico as an open market are multiplied by the opportunities offered by its internal market of more than 112 million people. Mexico is the 11th largest economy worldwide in terms of gross domestic product and the second in Latin America. Since Mexico is not the only country promoting an attractive business environment, it is more important than ever that it continues to improve its competitiveness. A failure to do so will be a missed opportunity. Business regulations are especially relevant because they are implemented by the government and have an immediate impact. Mexico City represents Mexico in the annual Doing Business report, which compares 183 economies worldwide. However, entrepreneurs across Mexico face different regulations and local practices depending on the state and city where they do business. Therefore, regulatory improvements require the coordination of the 3 levels of government: federal, state and municipal, and the support of the legislative and judicial bodies, as well as key stakeholders, such as notaries. In 2005, in an effort to examine this regulatory diversity, the Office of the President requested a study that will go beyond Mexico City. This led to the creation of the Doing Business in Mexico subnational series. Doing Business in Mexico 2012 is the fourth report in this series.